# Evaluate \int\frac{1}{(x^2+1)^2}dx

Evaluate $$\displaystyle\int{\frac{{{1}}}{{{\left({x}^{{2}}+{1}\right)}^{{2}}}}}{\left.{d}{x}\right.}$$

• Questions are typically answered in as fast as 30 minutes

### Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

nghodlokl
$$\displaystyle\int{\frac{{{\left.{d}{x}\right.}}}{{{\left({x}^{{2}}+{1}\right)}^{{2}}}}}$$
Set $$\displaystyle{x}\:={\tan{{\left({u}\right)}}}$$ and $$\displaystyle{\left.{d}{x}\right.}={{\sec}^{{2}}{\left({u}\right)}}{d}{u}$$. Then $$\displaystyle{\left({x}^{{2}}+{1}\right)}^{{2}}={\left({{\tan}^{{2}}{\left({u}\right)}}+{1}\right)}^{{2}}={{\sec}^{{4}}{\left({u}\right)}}$$ and $$\displaystyle{u}={\arctan{{\left({x}\right)}}}$$
$$\displaystyle=\int{{\cos}^{{2}}{\left({u}\right)}}{d}{u}={\frac{{{1}}}{{{2}}}}\int{\cos{{\left({2}{u}\right)}}}{d}{u}+{\frac{{{1}}}{{{2}}}}\int{1}{d}{u}$$
$$\displaystyle={\frac{{{u}}}{{{2}}}}+{\frac{{{1}}}{{{4}}}}{\sin{{\left({2}{u}\right)}}}+{C}$$
$$\displaystyle={\frac{{{x}^{{2}}{\arctan{{\left({x}\right)}}}+{x}+{\arctan{{\left({x}\right)}}}}}{{{2}{x}^{{2}}+{2}}}}+{C}$$
###### Not exactly what youâ€™re looking for?
Laura Worden
There is a faster way. Substitute
$$\displaystyle{x}={\tan{{\left({z}\right)}}}\ {\left.{d}{x}\right.}={{\sec}^{{2}}{\left({z}\right)}}{\left.{d}{z}\right.}$$
thus
$$\displaystyle{\left({x}^{{2}}+{1}\right)}^{{2}}={\left({{\tan}^{{2}}{\left({z}\right)}}+{1}\right)}^{{2}}={{\sec}^{{4}}{\left({z}\right)}}\ {z}={\arctan{{\left({x}\right)}}}$$
And remembering that
$$\displaystyle{\frac{{{1}}}{{{\sec}^{{2}}}}}={{\cos}^{{2}}}$$
$$\displaystyle\int{{\cos}^{{2}}{\left({z}\right)}}{\left.{d}{z}\right.}$$
Which is trivial and left to you.
The tangent/secant substitution is a great technique which most of people ignore. Study it, and you will solve lots of awesome integrals!
Final result:
$$\displaystyle{\frac{{{x}^{{2}}{\arctan{{\left({x}\right)}}}+{x}+{\arctan{{\left({x}\right)}}}}}{{{2}{x}^{{2}}+{2}}}}$$
star233

Let us find $$\frac{d[(ax+b)/(x^2+1)^n]}{dx}$$
$$=\frac{-ax^2-2bx+a}{(x^2+1)^{n+1}} \\=\frac{-a(x^2+1)-2bx+2a}{(x^2+1)^{n+1}} \\=-\frac{a}{(x^2+1)^n}+\frac{2a-2bx}{(x^2+1)^{n+1}}$$
Integrating both sides,
$$b=0\Rightarrow2\int\frac{dx}{(x^2+1)^{n+1}}=\int\frac{dx}{(x^2+1)^n}+\frac{x}{(x^2+1)^n} \\n=1\Rightarrow2\int\frac{dx}{(x^2+1)^2}=\int\frac{dx}{x^2+1}+\frac{x}{(x^2+1)}$$